PERAN GOOD CORPORATE GOVERNANCE DALAM MENCEGAH PRAKTIK FRAUD - Dina Ismaini; Rahmad Badri Jambi; Inal Syahputra; Karin Aribi Ivanka; Ahmad Wahyudi Zein (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Fraud is a serious issue that can disrupt the stability, credibility, and sustainability of organizations, particularly in corporate and financial sectors. Numerous fraud cases indicate that weak internal control systems and ineffective implementation of good corporate governance are major contributing factors to fraudulent practices. This study aims to analyze the role of Good Corporate Governance (GCG) in preventing fraud through a theoretical review and document-based analysis of relevant scholarly sources. The research employs a qualitative approach using library research or document analysis, drawing data from textbooks, national and international academic journals, regulatory frameworks, and previous research reports. The findings reveal that the implementation of GCG principles—namely transparency, accountability, responsibility, independence, and fairness—plays a significant role in strengthening internal control systems and fostering an integrity-based organizational culture. Good Corporate Governance functions not only as a regulatory framework but also as a preventive mechanism capable of reducing opportunities, pressures, and rationalizations that lead to fraud. Therefore, this study concludes that consistent and comprehensive implementation of Good Corporate Governance is a strategic instrument in fraud prevention and serves as a crucial foundation for establishing sound and sustainable organizational governance.